WOMEN ENTREPRENEURSHIP: A STUDY OF CHALLENGES FACED BY WOMEN’s IN MSMES of JAIPUR REGION IN RAJASTHAN - Kumari, Anjani; Thathera, Rajkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research will focus on analysing women entrepreneurs operating in Micro, Small, and Medium Enterprises in the Jaipur area of Rajasthan. This article focusses on the potential and obstacles of female entrepreneurship in the Jaipur area of Rajasthan. The survey includes women entrepreneurs who are both registered and unregistered. A cohort of 50 female entrepreneurs has been chosen for the research using a method known as judgemental sampling. This article aims to investigate the untapped challenges faced by women entrepreneurship for improving the economic support and to enhance women entrepreneurship in the Jaipur district of Rajasthan.